Augustine’s Theological Method And Contribution To The Christian Theology - Enggar Objantoro (International Journal of Indonesian Philosophy & Theology, 2020)
Today, the world is influenced by many views, such as secularism and atheism, which affect many people, so they are far from God.  Because of them, moral and ethical standards are not based on the belief of God, but just on the humanity standard.  For Christianity, the views cause many of God's believers to leave the Scripture's truths.  To solve the problem, Christians must learn from the Christian theologian who has a significant contribution to Christian theology.  One of the Christian theologians is Augustine.  Augustine was one of Christian’s famous theologians, in which his theology/thoughts are influenced Christian theology today.  This research uses a library research method to explore Augustine's ideas.  The books that expose about Augustine's views are used to find Augustine's theology.  The result of the research is that Augustine's theology is necessary and relevant to Christian's theology today to confront the world's views so that the people of God do not live far from God.